CREATING WARM ATMOSPHERE IN THE CLASS THROUGH GAMES. AIR POLLUTION - Shukurova Zamira Shodiyevna (Galaxy International Interdisciplinary Research Journal, 2023)
Games offer students a fun-filled and relaxing learning atmosphere. After learning and practicing new vocabulary, students have the opportunity to use language in non- stressful way. While playing games the learner′s attention is on the message, not on the language. Rather than pay attention to the correctness of linguistic forms, most participants will do all they can to win. This eases the fear of negative evaluation, the concern of being negatively judged in public, and which is one of the main factors inhibiting language learners from using the target language in front of other people.